Simulasi Kelayakan Ekonomi Pembangunan SPAM Regional II Berdasarkan Kerja Sama Pemerintah Dan Swasta (KPS) Dengan Melakukan Sharing Budget - Aditya Sukrama; Ari Sandhyavitri; Siswanto Siswanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The development of Water Supply System (SPAM) Regional II Riau Province requests high capital investment to build intake, transmition pipe lines, distribution pipe lines, water treatment plant and other related with infrastructure. Budget planbased on feasibility study which has been done is almost Rp 1,1 trillion that classified as very much, which resulted the payback periode is relatively long, whereas Bankonly allows refund with interest installment loan does not exceed a period of 10 years. However, it needs to simulate the economic feasibility of SPAM development based on public-private partnerships (PPP) by sharing budget. In other to financing the development of SPAM Regional II, the government of Riau Province collaborates this project’s financial with the scheme of Public Private Partnership (PPP). Therefore, several simulations of sharing budget need to beplanned for the continuity of infrastructure development. There are three alternatives in determining sharing budget, alternative I where government share (APBN andAPBD) is 30% of total budget plan while third party (private) share is 70%. Alternative II, from the government (APBN and APBD) is 40% and from the third party (Private) 60%, Alternative III of government (APBN and APBD) is 50%, whilefrom the third party (Private) 50%. Each of these three alternatives will also be three kinds of simulations loan funds performed on fonds that covered by the thirdparty,that is equity amounts of 30%, 50%, and 70% and the rest is Bank loans. By calculating the engineering economic analysis based on the sharing budget, it can be concluded that the third alternative with 30% bank loans (70% equity) is a simulation that results the best financial indicators such as NPV, BCR, PBP, and IRRKeywords : Budget Sharing, Public Private Partnership, financial indicators